Factors Affecting the Acceptance of Digitalization in the Automobile Aftermarket Industry - Basavarajappa, Rudresh S (Digital Repository of Theses - SSBM Geneva, 2024)
Recent trends in the automobile aftermarket industry such as, changes in the expectations of customers and generation of value; appearance of next-generation vehicles; and changes in competitive influence; indicate growing awareness of technology advancements and their implications in the business continuity and competitiveness in the automobile aftermarket. In this regard, there is a need for empirical scrutiny of the factors that impact acceptance of digitalization in this industry. This study pursued this scrutiny in the specific context of the aftermarket organisations related to off-highway vehicles (OHVs) using the Technology-Organization-Environment (TOE) framework for technology adoption as the underlying model to inform the study. The findings and recommendations resulting from the study can prospectively help organisations in the automobile aftermarket industry plan and prepare for technology adoption. Principally, the study provides insights for organisational stakeholders who have to develop an organisational strategy for digitalization adoption in their firms. The key facets to be considered in such a strategy include the complexity of digitalization and the technical competence of the firm, from a technological perspective; readiness (financial, technological, and organizational), from an organisational perspective; and the involvement/support of government and stakeholder pressure (from industry, competition, and suppliers), from the environmental perspective.